Intuitions of adult L2-Leamer and translation students as a guide to analysis in teaching - K., Connors (Glottodidactica, 1999)
This paper deals with the pedagogical implications of a series of studies on linguistic awareness. Adult learners, native- and near-native speakers of English were studied for their knowledge of equivalence and contrast relations between reflexive and emphatic -self constructions, on the one hand, and the possible interpretations of French pronominal-verbal constructions, on the other. In the pilot study, adult Francophone learners of English and an Anglophone control group judged the grammaticality of sets of sentences, one of which presented -self constructions that were grammatical as reflexives, as emphatics, as both, or as neither. The original purpose of this combination was to study the relation between objective ambiguity and grammaticality judgments. The results suggested not that syntactic ambiguity led to incorrect grammaticality judgments, but that garden-path (or “hard-to-get”) readings of constructions which globally are asymmetrically ambiguous are associated with incorrect judgments of ungrammaticality. That is, the only reading on which a given sub-type of construction is grammatical can be unknown to learners and even undetected by native speakers.